Predicting Rock-Eval® thermal analysis parameters of a soil layer based on samples from its sublayers; an experimental study on forest soils. (October 2021) - Kanari, Eva; Barré, Pierre; Baudin, François; Berthelot, Alain; Bouton, Nicolas; Gosselin, Frédéric; Soucémarianadin, Laure; Savignac, Florence; Cécillon, Lauric
Graphical abstract: Highlights: Rock-Eval® characterisation of a soil layer inferred from sublayers characteristics. Good additivity of Rock-Eval® parameters for temperate forest soils. Increasing clay content through mixing causes hydrocarbon retention during pyrolysis. Guidelines for harmonizing Rock-Eval® data from different soil depths. Abstract: Soil sampling depths strongly vary across soil studies. Stocks of elements (such as C, N) or organic matter in a soil layer can be simply calculated from stocks measured in its sublayers. This calculation is less obvious for other soil characteristics, such as soil organic carbon (SOC) persistence, complicating the comparison of results from different studies. Here, we tested whether Rock-Eval® parameters of a soil layer, characterizing soil organic matter and its biogeochemical stability, can be determined using Rock-Eval® data measured on its sublayers. Soil samples collected in 10 plots located in eight French forest sites, taken up at two different depths (0–30 cm, 30–50 cm), and their mixtures were analysed with Rock-Eval®. Expected values for the Rock-Eval® parameters of the soil mixtures were calculated either: (1) as the weighted mean of Rock-Eval® parameters measured on the two sublayers, or (2) based on a signal reconstructed as the weighted mean of Rock-Eval® thermograms recorded on the two sublayers. Our results showed a good agreement between measured and expected Rock-Eval® parameter values. However, when the clay content strongly differed between the two soil sublayers, the amount of pyrolyzed hydrocarbons measured on the soil mixtures was slightly lower than expected. We conclude that it is reasonable to calculate Rock-Eval® parameters of a soil layer, from the Rock-Eval® signature of its sublayers. Our findings facilitate the harmonization of Rock-Eval® data from large scale soil studies using different sampling depths.